2021
DOI: 10.3233/jad-200964
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid C18 Ceramide Associates with Markers of Alzheimer’s Disease and Inflammation at the Pre- and Early Stages of Dementia

Abstract: Background: Understanding how dysregulation in lipid metabolism relates to the severity of Alzheimer‘s disease (AD) pathology might be critical in developing effective treatments. Objective: To identify lipid species in cerebrospinal fluid (CSF) associated with signature AD pathology and to explore their relationships with measures reflecting AD-related processes (neurodegeneration, inflammation, deficits in verbal episodic memory) among subjects at the pre- and early symptomatic stages of dementia. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 86 publications
3
10
0
Order By: Relevance
“…Among the screened metabolites, glucosylceramides, lysophosphatidylcholines, and triacylglycerides were shown to be associated with CSF Aβ, while sphingomyelins and ceramides were found to be associated with CSF total tau and brain atrophy. Similarly, Teitsdottir et al (26) examined 60 individuals from an Icelandic memory clinic and reported that ceramide C18 was a distinguishing factor between AD patients and controls, a finding previously described elsewhere. Ceramides are second messengers that are created via sphingomyelin breakdown or synthesis from serine and palmitate.…”
Section: Metabolomicssupporting
confidence: 56%
“…Among the screened metabolites, glucosylceramides, lysophosphatidylcholines, and triacylglycerides were shown to be associated with CSF Aβ, while sphingomyelins and ceramides were found to be associated with CSF total tau and brain atrophy. Similarly, Teitsdottir et al (26) examined 60 individuals from an Icelandic memory clinic and reported that ceramide C18 was a distinguishing factor between AD patients and controls, a finding previously described elsewhere. Ceramides are second messengers that are created via sphingomyelin breakdown or synthesis from serine and palmitate.…”
Section: Metabolomicssupporting
confidence: 56%
“…While the relationship between sphingolipid dysregulation was established in AD, there is still uncertainty regarding the exact lipid species that are directly involved in neurodegeneration. It was collectively established that accumulation of Cer C16, C18 and C20 is a trait of AD patients [28][29][30][31]; however, the presence of very long chains Cers (C22 and C24) was observed for the first time in iNPH only and appeared to characterize this disorder. It is tempting to associate this feature to a protective role of these species toward APP and BACE1, inflammation, ER stress and ROS generation supported by proteomic data and from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The current study cohort and the selection criteria have been described earlier (Teitsdottir et al, 2020 , 2021 ). Subjects were recruited from the Icelandic MCI study cohort ( n = 165).…”
Section: Methodsmentioning
confidence: 99%
“…The collection of CSF and the measurements of protein concentrations have previously been described (Teitsdottir et al, 2020 , 2021 ). Collection of CSF was done via lumbar puncture with a 22-gauge spinal needle at the L3/4 or L4/5 interspace.…”
Section: Methodsmentioning
confidence: 99%